Feeding India’s babies: Insights on trends and patterns from the National Family Health Surveys, 2015-16 to 2019-21 - Ray, Soumyajit; Ashok, Sattvika; Avula, Rasmi; Nguyen, Phuong Hong; Hemalatha, R.; Singh, S. K.; Chamois, Sylvie; Menon, Purnima (International Food Policy Research Institute, 2023)
Early life nutrition sets the stage for the health, nutrition, and development of young children. Optimal infant and young child feeding (IYCF) practices begin with timely initiation of breastfeeding, followed by exclusive breastfeeding and complementary feeding. This Data Note provides an overview of trends and patterns in IYCF practices in India at the national-, state-, and district levels based on the 2015-16 and 2019-21 National Family Health Surveys (NFHS) data. IYCF indicators were created following World Health Organization and UNICEF’s 2021 guidelines.